<span>To answer this question, you need to multiply the number inside the bracket first. Then you can move the number to the right side of the equal sign and keep the x on the left side of the equal sign. The step would be like this
2(x – 5) - 6x= -22
(2x - 10) - 6x = -22
2x - 6x = -22 +10
-4x= -12
x= -12/-4
x=3</span>
Answer:
Step-by-step explanation:
hello :
x3^-8=0 means : x3^=8
but : 8 = 2^3
so : x3^= 2^3
x=2
Answer:
the anser is 7 :)
Step-by-step explanation:
Answer:
f(2)=7
f(-1)=+1
Step-by-step explanation:
f (2)= 2³-2²+3 =8-4+3=7
f (-1)= (-1)³-(-1)²+3= -1- (+1) +3= -1-1+3=+1
Answer:
x = 30 in
Step-by-step explanation:
length of rectangle is (2/3)x + 10; width is (1/3)x + 5;
perimeter is 90 in; find x:
P = 90 in = 2(2/3)x + 2(10) + 2(1/3)x + 2(5), or
90 in = (6/3)x + 30 in
Solving for x, we get (2)x = 60 in, or x = 30 in